2020
DOI: 10.15560/16.3.749
|View full text |Cite
|
Sign up to set email alerts
|

First report of Coenosia attenuata (Stein, 1903) (Diptera, Muscidae) in Uruguay, confirmed by DNA barcode sequences

Abstract: Coenosia attenuata (Stein, 1903) is a predatory fly which feeds on other insects and can be used as a possible biological control agent. We report this insect in Uruguay for the first time. The flies were found in greenhouses on tomatoes and sweet peppers and identified using both DNA barcoding and morphological characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
1
0
0
Order By: Relevance
“…Body length and body weight of adult C. attenuata, D. melanogaster and B. impatiens were analyzed in our study to better understand the complexity of predation. We report body length and body weight of adult C. attenuata from Tianjin to be similar to those reported by us previously [17,39] and to those reported in Uruguay where the C. attenuata flies measured approximately 2.5-5.00 mm in length [47]. Body weight of adult D. melanogaster measured in this study is similar to those reported by Chen et al (2019) [48].…”
Section: Discussionsupporting
confidence: 90%
“…Body length and body weight of adult C. attenuata, D. melanogaster and B. impatiens were analyzed in our study to better understand the complexity of predation. We report body length and body weight of adult C. attenuata from Tianjin to be similar to those reported by us previously [17,39] and to those reported in Uruguay where the C. attenuata flies measured approximately 2.5-5.00 mm in length [47]. Body weight of adult D. melanogaster measured in this study is similar to those reported by Chen et al (2019) [48].…”
Section: Discussionsupporting
confidence: 90%